Euglenatides, Potent Antiproliferative Cyclic Peptides Isolated from the Freshwater Photosynthetic Microalga Euglena gracilis. Issue 23 (6th April 2022) - Aldholmi, Mohammed; Ahmad, Rizwan; Carretero‐Molina, Daniel; Pérez‐Victoria, Ignacio; Martín, Jesús; Reyes, Fernando; Genilloud, Olga; Gourbeyre, Léa; Gefflaut, Thierry; Carlsson, Hanne; Maklakov, Alexei; O'Neill, Ellis; et al.
Abstract: By limiting the nitrogen source to glutamic acid, we isolated cyclic peptides from Euglena gracilis containing asparagine and non‐proteinogenic amino acids. Structure elucidation was accomplished through spectroscopic methods, mass spectrometry and chemical degradation. The euglenatides potently inhibit pathogenic fungi and cancer cell lines e.g., euglenatide B exhibiting IC50 values of 4.3 μM in Aspergillus fumigatus and 0.29 μM in MCF‐7 breast cancer cells. In an unprecedented convergence of non‐ribosomal peptide synthetase and polyketide synthase assembly‐line biosynthesis between unicellular species and the metazoan kingdom, euglenatides bear resemblance to nemamides from Caenorhabditis elegans and inhibited both producing organisms E. gracilis and C. elegans . By molecular network analysis, we detected over forty euglenatide‐like metabolites in E. gracilis, E. sanguinea and E. mutabilis, suggesting an important biological role for these natural products. Abstract : Light and glutamic acid induced E. gracilis to produce euglenatides with antifungal and anticancer activity. Euglenatides were also detected in E. sanguinea and E. mutabilis . They resemble the nemamides isolated from C. elegans, inhibited both producing species, and represent uniquely convergent assembly‐line biosynthesis between unicellular organisms and metazoans.